2016
DOI: 10.7205/milmed-d-15-00185
|View full text |Cite
|
Sign up to set email alerts
|

An Interim LAeq8 Criterion for Impulse Noise Injury

Abstract: Therefore, considering the limitation of the walk-up dataset, it is conservative to adopt the 85 dBA threshold for general application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…20,21 Waveform parameterbased damage risk criteria are typically quantified in terms of the peak amplitude, pressure wave, and envelope duration of the impulse. 22 Other damage risk criteria reference the energy-based, integrated A-weighted 8-hour equivalent level, [23][24][25] apply criteria derived from theoretical physiologically based ear models such as the Auditory Hazard Assessment Algorithm for Humans, 26 or apply fatigue modeling to predict cochlear structure damage. 27 These more complex approaches are typically utilized for research or military purposes and, once validated fully, could better inform health care providers and the public.…”
Section: Auditory Risk From Firearm Impulse Noisementioning
confidence: 99%
“…20,21 Waveform parameterbased damage risk criteria are typically quantified in terms of the peak amplitude, pressure wave, and envelope duration of the impulse. 22 Other damage risk criteria reference the energy-based, integrated A-weighted 8-hour equivalent level, [23][24][25] apply criteria derived from theoretical physiologically based ear models such as the Auditory Hazard Assessment Algorithm for Humans, 26 or apply fatigue modeling to predict cochlear structure damage. 27 These more complex approaches are typically utilized for research or military purposes and, once validated fully, could better inform health care providers and the public.…”
Section: Auditory Risk From Firearm Impulse Noisementioning
confidence: 99%
“…There are also data according to which the A-weighted SPL, which guarantees no impact of noise on hearing even after long-term exposure, is 80 dB [20]. At the same time, L EX,8h at 89 dB can be supplemented since one of the papers concluded that, in the case of impulse noise [21], this was considered a safe value to protect 95% of the population in 95% of cases.…”
Section: Methodsmentioning
confidence: 99%
“…In spite of the use of hearing protectors, exposure to impulse noise may be dangerous to hearing [9]. Therefore, a better and safer solution is the use of devices which reproduce human characteristics, which eliminates the need for human participation in the tests [10,11]. These devices are called acoustic test fixtures.…”
Section: Introductionmentioning
confidence: 99%